The far-ultraviolet continuum slope as a Lyman Continuum escape estimator at high redshift. Issue 4 (7th October 2022) - Chisholm, J; Saldana-Lopez, A; Flury, S; Schaerer, D; Jaskot, A; Amorín, R; Atek, H; Finkelstein, S L; Fleming, B; Ferguson, H; Fernández, V; Giavalisco, M; et al.
ABSTRACT: Most of the hydrogen in the intergalactic medium (IGM) was rapidly ionized at high redshifts. While observations have established that reionization occurred, observational constraints on the high-redshift ionizing emissivity remain elusive. Here, we present a new analysis of the Low-redshift Lyman Continuum Survey (LzLCS) and literature observations, a combined sample of 89 star-forming galaxies at redshifts near 0.3 with Hubble Space Telescope observations of their ionizing continua (or Lyman Continuum, LyC). We find a strong (6σ significant) inverse correlation between the continuum slope at 1550 Å (defined as F_λ λ ^β ^1550_obs ) and both the LyC escape fraction ( f esc, LyC ) and f esc, LyC times the ionizing photon production efficiency (ξion ). On average, galaxies with redder continuum slopes have smaller f esc, LyC than galaxies with bluer slopes mainly due to higher dust attenuation. More than 5 per cent (20 per cent) of the LyC emission escapes galaxies with β _obs^1550 <−2.1 (−2.6). We find strong correlations between β _obs^1550 and the [O iii ]/[O ii ] flux ratio (at 7.5σ significance), galaxy stellar mass (at 5.9σ), the gas-phase metallicity (at 4.6σ), and the observed far-ultraviolet absolute magnitude (at 3.4σ). Using previous observations of β _obs^1550 at high redshift, we estimate the evolution of f esc, LyC with both redshift and galaxy magnitude. The LzLCS observations suggest that fainter and lower mass galaxies dominate the ionizing photon budget at higher redshift, possibly due to their rapidly evolving metal and dust content. Finally, we use our correlation between β _obs^1550 and f esc, LyC × ξion to predict the ionizing emissivity of galaxies during the epoch of reionization. Our estimated emissivities match IGM observations, and suggest that star-forming galaxies emit sufficient LyC photons into the IGM to exceed recombinations near redshifts of 7–8.